Experimental and CFD Analysis of Circular Labyrinth Weirs - Bilhan, Omer; Aydin, M. Cihan; Emiroglu, M. Emin; Miller, Carol J. (Asce-Amer Soc Civil Engineers, 2018)
Labyrinth weirs present an effective solution for high discharge efficiency in space-restrictive situations. However, these weirs exhibit negative effects (vibrations, noise, and instability) when the nappe clings to the downstream surface of the weir because of subatmospheric pressures. Nappe breakers are used to limit the occurrence of this behavior. Currently, only a limited number of investigations have focused on the performance of nappe breakers when applied to circular labyrinth weirs. The present study has been designed to provide detailed performance data for sharp-crested circular labyrinth weirs for the case of a simple weir as well an augmented weir (with nappe breaker). Three-dimensional (3D) computational fluid dynamics (CFD) models were verified by comparison with the experimental observations, and then the pressures under the jet flow at the downstream of the weir were scrutinized using a two-phase (water-air) turbulent numerical model. The results of both the numerical simulations and experimental observations confirm the positive outcomes obtained through the use of the nappe breakers to control subatmospheric pressures on the downstream face of the weir. (C) 2018 American Society of Civil Engineers.
Keywords: Circular labyrinth weir; Computational fluid dynamics (CFD); Two-phase flow; Nappe breaker